Kinematic analysis of the shot-put: A method of assessing the mechanical work of the hand action force - Landolsi, M.; Labiadh, L.; Zarrouk, F.; Maaref, K.; Ghannouchi, S.; Tabka, Z.; Lacouture, P. (European Journal of Sport Science, 2018)
The aims of this study were to (1) propose a method for evaluating shot-putters mechanical power, (2) investigate the relationship between mechanical work of hand action force (WHAF), peak power output (PPO) of different limbs and shot-put performance and (3) show which of these two parameters (WHAF, PPO) were the most appropriate to characterize the explosive abilities of the shot-putter. Twelve junior right-handed shot-putters, practised glide technique shot-put throwers (personal best = 13.57 ± 1.72 m), participated in this study. Arm and leg force-velocity tests were performed to measure PPO. Kinematic analysis was conducted during a shot-putting event in regular conditions to quantify the WHAF at the release moment and shot-put performance. Significant correlations were found between absolute arm and leg PPO with upper and lower muscle volumes (r = .67; p = .03; r = .76; p = .01; r = .74, p = .01; r = .65, p = .04). Positive relationships were recorded between absolute arm and leg PPO and shot-put performance (r = .67, p = .02; r = .81, p = .004, respectively). Shot-put performance was also closely related to the WHAF (r = .93, p = .0001) and release velocity parameter (r = .86, p = .001). The present results confirm that force-velocity test and WHAF constitute useful tools for assessing mechanical power in throwing. The WHAF could be considered as more suitable than force-velocity test.